From the Extended Mind to the Digitally Extended Self: A Phenomenological Critique - Federica Buongiorno (Aisthesis, 2019)
In this paper, I will critically consider Clark and Chalmers’ hypothesis of the «extended mind» in order to sketch a possible phenomenological account of active externalism, by following three steps: (i) I will consider Clark and Chalmers’ hypothesis within the broader context of the so-called «physical symbol system hypothesis» theorized by Herbert A. Simon; (ii) I will connect the problem of the «extended mind» to that of the «extended self», with particular regard to the context of digitalization; (iii) I will take into account an explanatory dimension that has been fundamentally underrated by externalist theories: the dimension of the human body and its relationship to mind, which I understand from a phenomenological perspective. My ultimate goal is to show how phenomenology could provide the missing theoretical framework to develop a more complex and comprehensive theory of the (digitally) extended self.